A kind of anti-efflorescence composite layer and its preparation method and application

By adopting a multi -level structure of anti -puzzle composite layer on the building wall, the long -term effects of pan -alkali problems in existing technologies have been solved, and excellent closed and anti -pantrocytic properties are achieved, ensuring the beauty and structure of the wall surface Safety.

CN112761316BActive Publication Date: 2025-01-28FIRST NEW MATERIAL TECH DEV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202011579190.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-28
Publication Date
2025-01-28
Estimated Expiration
2040-12-28

AI Technical Summary

Technical Problem

The existing technology has poor long-term effectiveness in preventing building walls from being overly alkaline and cannot play a closed role for a long time. Especially in environments with high humidity, there is still a problem of overly alkaline, which affects the decorative effect and structural safety.

Method used

A multi -level structure of anti -pistol composite layer is adopted, including the insulation layer, mortar layer, hydrophobic bottom paint layer, putty layer, waterproof bottom paint layer, bottom paint layer, and facial paint layer. Effectively prevent external moisture from penetration and the precipitation of grassroots water vapor.

Benefits of technology

Achieve excellent closed effects and anti -alkali properties, ensure the aesthetics of the wall coating and the safety of the wall. The pan -alkali area continues to wet from 10%or even as low as 5%after 24 hours. In the traditional primer and facial paint coating system, the resistance of alkali was increased by 70-95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112761316B_ABST
    Figure CN112761316B_ABST
Patent Text Reader

Abstract

The present invention provides an anti-efflorescence composite layer and a preparation method and application thereof, wherein the anti-efflorescence composite layer comprises an insulation layer, a mortar layer, a hydrophobic primer layer, a putty layer, a waterproof primer layer, a primer layer and a topcoat layer arranged in sequence. The anti-efflorescence composite layer can effectively prevent the infiltration of external moisture and the precipitation of water vapor from the base layer through the selection of materials and the setting of a hierarchical structure, has an excellent sealing effect and anti-efflorescence performance, and fully ensures the aesthetics of the wall coating and the safety of the wall. At the same time, the preparation process of the anti-efflorescence composite layer is simple, the raw material cost is low, and it has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to an anti-efflorescence composite layer and a preparation method and application thereof. Background Art

[0002] Efflorescence is one of the common problems in cement-based products such as building walls. After efflorescence, a layer of white flakes, scales or needle-like crystals is produced on the decorative surface, causing the decorative surface coating to discolor, fade, fall off and become flowery, which not only seriously affects the appearance of the building wall, but also affects the hardness of the wall. If the efflorescence problem is not handled in time, it may even accelerate the destruction of the structure and bring safety hazards. The causes of efflorescence include: the capillary phenomenon of the pores inside the substrate causes calcium hydroxide to migrate to the surface; the wall has a high moisture, alkali or salt content, and the water vapor evaporates and brings out the salt and alkali and precipitates on the bottom layer or surface of the paint film; water vapor or rainwater enters the wall through the gap and brings out the salt and alkali when it diffuses; the base is severely powdered or there are components such as grease and release agent. Due to the above reasons, traditional mortar cement-based walls cannot fundamentally eliminate the efflorescence phenomenon. Therefore, it is necessary to rely on primer to seal or reinforce the base layer to achieve the effect of anti-efflorescence.

[0003] CN105440853A discloses a long-lasting anti-efflorescence primer, which is formulated from the following components: water, cellulose, pH regulator, wetting agent, dispersant, filler, pure acrylic emulsion, film-forming aid, antifreeze, bactericide, mildewcide, defoamer and thickener, wherein the filler includes zinc oxide. The primer overcomes the shortcomings of the existing exterior wall primer in terms of anti-efflorescence and poor salting out through formula screening, and can actively prevent paint film efflorescence. CN105482570A discloses an exterior wall alkali-resistant primer and a preparation method thereof, wherein the exterior wall alkali-resistant primer comprises, by mass percentage, 30-45% of water-based primer emulsion, 5.1-12% of pigment, 15-35% of filler, 0.1-0.2% of wetting agent, 0.3-0.6% of dispersant, 0.05-0.15% of pH regulator, 0.1-0.5% of defoamer, 0.1-0.3% of preservative, 0.1-0.3% of hydroxyethyl cellulose, 0.2-0.6% of thickener, 2.6-4% of film-forming aid, 0.1-0.2% of antifreeze agent, 2-5% of slow-release naphthalene-based water reducer, and 18-25% of water. The primer is used for exterior wall putty or mortar, can play a role in sealing the alkalinity of the base layer, and reduce the defects of the paint film caused by efflorescence. CN103483968A discloses a water-based alkali-resistant and salting-out-resistant sealing primer, which consists of component A and component B, wherein component A comprises, by weight percentage, 50% of tert-butyl carbonate and 50% of butyl acrylate; component B comprises, by weight percentage, 25-30% of water, 0.1-0.2% of bactericide, 0.4-0.6% of dispersant, 0.05-0.1% of wetting agent, 0.3-0.5% of defoamer, 0.2-0.4% of propylene glycol, 6-10% of talc, 6-10% of heavy calcium, 25-35% of epoxy alkali-resistant primer emulsion, 5-15% of emulsifier, 10-15% of antifreeze agent, 0.5-1.0% of film-forming aid and 0.1-0.5% of leveling agent; the primer has not only alkali-resistant and salt-resistant properties, but also crack-resistant and impermeability-resistant properties, and can improve the alkali-resistant and salting-out-resistant properties of wall concrete or cement mortar.

[0004] Most of the primers represented by the above-mentioned primers achieve anti-efflorescence by filling the pore structure of cement concrete, which can only alleviate the efflorescence phenomenon to a certain extent. However, their long-term anti-efflorescence effect is not good, they cannot play a sealing role for a long time, and it is difficult to block water vapor. In specific environments such as high humidity, there is still efflorescence problem, and they have certain limitations in use.

[0005] Therefore, it is an urgent problem to be solved in the art to develop a material or layered structure that can exert an anti-efflorescence effect in a long-term and stable manner to ensure the safety and decorative value of the wall. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an anti-efflorescence composite layer and a preparation method and application thereof. Through the selection of materials and the setting of a hierarchical structure, the anti-efflorescence composite layer can effectively prevent the infiltration of external moisture and the precipitation of water vapor from the base layer, has excellent sealing effect and anti-efflorescence performance, and fully ensures the aesthetics of the wall coating and the safety of the wall.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an anti-efflorescence composite layer, which includes an insulation layer, a mortar layer, a hydrophobic primer layer, a putty layer, a waterproof primer layer, a primer layer and a topcoat layer arranged in sequence.

[0009] The structural schematic diagram of the anti-efflorescence composite layer provided by the present invention is as follows Figure 1 As shown, it includes an insulation layer 1, a mortar layer 2, a hydrophobic primer layer 3, a putty layer 4, a waterproof primer layer 5, a primer layer 6 and a topcoat layer 7 arranged in sequence; wherein the hydrophobic primer layer is arranged on the side of the putty layer close to the substrate, and has a hydrophobic property, which can prevent the water vapor of the base layer from diffusing and penetrating, and at the same time will not affect the air permeability (air) of the coating. The waterproof primer layer arranged on the side of the putty layer close to the outside can prevent the outside moisture from entering the inside of the composite layer, and avoid efflorescence caused by water absorption by the putty layer and the mortar layer. The anti-efflorescence composite layer has excellent waterproof and water-blocking effects and anti-efflorescence properties through the combination and compounding of each layer, thereby ensuring the aesthetics of the wall coating and the safety of the wall.

[0010] Preferably, the thickness of the insulation layer is 30-80 mm, for example, it can be 32 mm, 35 mm, 38 mm, 40 mm, 40 mm, 45 mm, 48 mm, 50 mm, 52 mm, 55 mm, 58 mm, 60 mm, 62 mm, 65 mm, 68 mm, 70 mm, 72 mm, 75 mm or 78 mm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0011] Preferably, the material of the thermal insulation layer is a thermal insulation board.

[0012] Preferably, the insulation board comprises a polystyrene insulation board.

[0013] Preferably, the thickness of the mortar layer is 2 to 3 mm, for example, it can be 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm or 2.9 mm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0014] Preferably, the material of the mortar layer includes a combination of silicate cement, quartz sand and glue powder.

[0015] Preferably, the thickness of the hydrophobic primer layer is 5 to 20 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or 19 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0016] Preferably, the material of the hydrophobic primer layer is a hydrophobic primer, and the hydrophobic primer comprises the following components in parts by weight: 30 to 50 parts of acrylic emulsion, 0.5 to 5 parts of film-forming aid and 0.1 to 2 parts of silicone hydrophobic agent.

[0017] In the hydrophobic primer, the acrylic emulsion is 30 to 50 parts, for example, it can be 31 parts, 33 parts, 35 parts, 37 parts, 39 parts, 40 parts, 41 parts, 43 parts, 45 parts, 47 parts or 49 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0018] The film-forming aid is 0.5 to 5 parts, for example, it can be 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts or 4.8 parts, as well as specific point values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0019] The organosilicon hydrophobic agent is 0.1 to 2 parts, for example, it can be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts or 1.8 parts, as well as specific point values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0020] Preferably, the acrylic emulsion includes pure acrylic emulsion and / or styrene acrylic emulsion.

[0021] Preferably, the film-forming aid is an alcohol ester film-forming aid.

[0022] Preferably, the organosilicon hydrophobic agent comprises polysiloxane.

[0023] Preferably, the hydrophobic primer further comprises 0.01 to 0.3 parts of defoamer by weight, for example, the defoamer may be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts or 0.28 parts, etc.

[0024] Preferably, the hydrophobic primer also includes 0.1 to 3 parts of antifreeze by weight, for example, the antifreeze may be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts or 2.8 parts, etc.

[0025] Preferably, the hydrophobic primer further comprises 0.01 to 0.3 parts of preservatives by weight, for example, the preservatives may be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts or 0.28 parts, etc.

[0026] Preferably, the hydrophobic primer further comprises a solvent, and the solvent is water.

[0027] As a preferred technical solution of the present invention, the hydrophobic primer comprises the following components in parts by weight: 30 to 50 parts of acrylic emulsion, 0.5 to 5 parts of film-forming aid, 0.1 to 2 parts of silicone hydrophobic agent, 0.01 to 0.3 parts of defoaming agent, 0.1 to 3 parts of antifreeze agent and 0.01 to 0.3 parts of preservative, and water is added to 100 parts.

[0028] Preferably, the thickness of the putty layer is 1 to 2 mm, for example, it can be 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm or 1.9 mm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0029] Preferably, the material of the putty layer includes a combination of silicate cement, heavy calcium powder and rubber powder.

[0030] Preferably, the thickness of the waterproof primer layer is 5 to 20 μm, for example, it can be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or 19 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0031] Preferably, the material of the waterproof primer layer is a waterproof primer, which includes 40 to 60 parts (for example, 41 parts, 43 parts, 45 parts, 47 parts, 49 parts, 50 parts, 51 parts, 53 parts, 55 parts, 57 parts or 59 parts, etc.) of acrylic waterproof emulsion and 0.5 to 5 parts (for example, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts or 4.8 parts, etc.) of film-forming aid in parts by weight.

[0032] Preferably, the water absorption rate of the acrylic waterproof emulsion is 0-0.1%, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08% or 0.09%.

[0033] In the present invention, the water absorption rate of the acrylic waterproof emulsion is tested by the following method: a wet film of the emulsion with a thickness of 250 μm is prepared on a glass plate of known weight, and dried at 50° C. for 48 hours; then the glass plate and the emulsion film are completely immersed in deionized water for 24 hours. The glass plate is taken out, the clear water on the surface is wiped off, and the mass difference before and after the glass plate and the emulsion film are tested, and the water absorption rate of the emulsion can be calculated.

[0034] Preferably, the number average molecular weight of the acrylic waterproof emulsion is 800,000 to 1.2 million, for example, it can be 820,000, 850,000, 880,000, 900,000, 920,000, 950,000, 980,000, 1,020,000, 1,050,000, 1,080,000, 1,100,000, 1,120,000, 1,150,000 or 1,180,000.

[0035] Preferably, the glass transition temperature of the acrylic waterproof emulsion is -15 to 0°C, for example, -14°C, -13°C, -12°C, -11°C, -10°C, -9°C, -8°C, -7°C, -6°C, -5°C, -4°C, -3°C, -2°C or -1°C, etc.

[0036] As a preferred technical solution of the present invention, the material of the waterproof primer layer is a waterproof primer, and the film-forming substance of the waterproof primer is an acrylic waterproof emulsion. After the acrylic waterproof emulsion is dried and solidified, a waterproof primer layer with a dense structure is formed, thereby effectively blocking external moisture and preventing moisture from entering the interior of the composite layer, thereby achieving an anti-efflorescence effect.

[0037] Preferably, the film-forming aid is an alcohol ester film-forming aid.

[0038] Preferably, the waterproof primer also includes 0.1 to 3 parts of antifreeze by weight, for example, the antifreeze may be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts or 2.8 parts, etc.

[0039] Preferably, the waterproof primer also includes 0.01 to 0.3 parts of defoaming agent by weight, for example, the defoaming agent can be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts or 0.28 parts, etc.

[0040] Preferably, the waterproof primer also includes 0.01 to 0.3 parts of preservatives by weight, for example, the preservatives may be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.18 parts, 0.2 parts, 0.22 parts, 0.25 parts or 0.28 parts, etc.

[0041] Preferably, the waterproof primer also includes a solvent, and the solvent is preferably water.

[0042] As a preferred technical solution of the present invention, the waterproof primer comprises the following components in parts by weight: 40 to 60 parts of acrylic waterproof emulsion, 0.5 to 5 parts of film-forming aid, 0.1 to 3 parts of antifreeze agent, 0.01 to 0.3 parts of defoaming agent and 0.01 to 0.3 parts of preservative, and water is added to 100 parts.

[0043] Preferably, the thickness of the primer layer is 5 to 20 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or 19 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0044] Preferably, the primer layer is an acrylic primer layer.

[0045] Preferably, the thickness of the topcoat layer is 80 to 100 μm, for example, it may be 81 μm, 83 μm, 85 μm, 87 μm, 89 μm, 90 μm, 91 μm, 93 μm, 95 μm, 97 μm or 99 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0046] Preferably, the material of the topcoat layer is water-based acrylic topcoat.

[0047] Exemplarily, the water-based acrylic topcoat includes acrylic emulsion, titanium dioxide, filler and additives; the additives include any one or a combination of at least two of a film-forming aid, a wetting agent, a dispersant, a defoamer, a leveling agent, a preservative, a pH regulator, a thickener or an antifreeze agent. The water-based acrylic topcoat can be purchased from the market.

[0048] In another aspect, the present invention provides a method for preparing the anti-efflorescence composite layer as described in the first aspect, the preparation method comprising the following steps:

[0049] (1) After attaching the insulation board to the substrate, apply mortar on the insulation board and dry it to obtain a mortar layer;

[0050] (2) coating a hydrophobic primer on the mortar layer obtained in step (1), drying the mortar layer, and obtaining a hydrophobic primer layer; coating putty on the hydrophobic primer layer, curing the mortar layer, and obtaining a putty layer;

[0051] (3) coating a waterproof primer on the putty layer obtained in step (2), and coating a primer after drying; coating a topcoat after the primer layer obtained is dried, and drying to obtain the anti-efflorescence composite layer.

[0052] Preferably, the substrate in step (1) is a wall.

[0053] Preferably, the drying time in step (1) is 0.5 to 15 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h or 14 h, etc.

[0054] Preferably, the drying time in step (2) is 0.5 to 15 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h or 14 h, etc.

[0055] Preferably, the curing time in step (2) is 12 to 48 hours, for example, 13 hours, 15 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours or 46 hours.

[0056] Preferably, the drying and curing in the preparation method are both carried out at room temperature.

[0057] In another aspect, the present invention provides a use of the anti-efflorescence composite layer as described in the first aspect in painting of building walls.

[0058] Preferably, the building wall is an external wall of a building.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] The anti-efflorescence composite layer provided by the present invention comprises an insulation layer, a mortar layer, a hydrophobic primer layer, a putty layer, a waterproof primer layer, a primer layer and a topcoat layer arranged in sequence. Through the screening of materials at each level and the compounding arrangement of the hierarchical structure, it can effectively prevent the infiltration of external moisture and the precipitation of water vapor at the base layer, and has excellent sealing effect and anti-efflorescence performance. The anti-efflorescence composite layer is further optimized through the hierarchical design and the material, so that the efflorescence area of ​​the anti-efflorescence composite layer after continuous water wetting for 24 hours is less than 10%, or even as low as less than 5%, and the anti-efflorescence performance is improved by 70-95% relative to the traditional primer and topcoat coating system, and the anti-efflorescence composite layer has good construction performance, good recoatability and interlayer adhesion between the levels, good mechanical properties, and fully ensures the aesthetics of the wall coating and the safety of the wall. The preparation process of the anti-efflorescence composite layer is simple, the raw material cost is low, and it has good application prospects, and is particularly suitable for the coating of building exterior walls. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 A schematic diagram of the structure of the anti-efflorescence composite layer provided by the present invention, wherein 1-insulation layer, 2-mortar layer, 3-hydrophobic primer layer, 4-putty layer, 5-waterproof primer layer, 6-primer layer, 7-topcoat layer;

[0062] Figure 2 It is a comparison chart of the efflorescence test of the anti-efflorescence composite layer of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0063] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0064] The raw materials involved in the following embodiments and comparative examples of the present invention include:

[0065] (1) Acrylic emulsion: styrene acrylic emulsion, Badufu 309;

[0066] (2) Silicone hydrophobic agent, Wacker BS1306;

[0067] (3) Acrylic waterproof emulsion: Baderfu 790, water absorption rate is 0.1%, number average molecular weight is 1 million, and glass transition temperature is -10°C;

[0068] (4) Film-forming aid: alcohol ester film-forming aid, Eastman OE400;

[0069] (5) Defoamer: mineral oil defoamer, Nopco NXZ;

[0070] (6) Preservatives: isothiazolinone preservatives, Dow LXE;

[0071] (7) Antifreeze: industrial grade propylene glycol.

[0072] Example 1

[0073] An anti-efflorescence composite layer, the structural schematic diagram is as follows Figure 1 As shown, the following layers are arranged in sequence:

[0074] Insulation layer 1, thickness 50 mm, polystyrene insulation board;

[0075] Mortar layer 2, thickness is 2mm, material is Fusite BS202 mortar;

[0076] The hydrophobic primer layer 3 has a thickness of 10 μm, and the materials of the hydrophobic primer layer include, by weight: 40 parts of acrylic emulsion, 2 parts of film-forming aid, 1 part of organosilicon hydrophobic agent, 0.1 part of defoaming agent, 1 part of antifreeze agent and 0.1 part of preservative;

[0077] Putty layer 4, thickness is 2mm, material is Fusite GN840 putty;

[0078] The waterproof primer layer 5 has a thickness of 10 μm, and the materials of the waterproof primer layer include, by weight: 50 parts of acrylic waterproof emulsion, 2 parts of film-forming aid, 1 part of antifreeze agent, 0.1 part of defoamer and 0.1 part of preservative;

[0079] Primer layer 6, thickness is 10 μm, made of Fusite E100 primer;

[0080] The topcoat layer 7 has a thickness of 90 μm and is made of Fusite E165 topcoat.

[0081] The preparation method of the anti-efflorescence composite layer is as follows:

[0082] (1) 40 parts of acrylic emulsion, 2 parts of film-forming aid, 1 part of silicone hydrophobic agent, 0.1 part of defoamer, 1 part of antifreeze agent and 0.1 part of preservative are mixed, water is added to 100 parts, and the mixture is evenly dispersed to obtain a hydrophobic primer; 50 parts of acrylic waterproof emulsion, 2 parts of film-forming aid, 1 part of antifreeze agent, 0.1 part of defoamer and 0.1 part of preservative are mixed, water is added to 100 parts, and the mixture is evenly dispersed to obtain a waterproof primer;

[0083] (2) a polystyrene insulation board (with a specification of 1200 mm×2400 mm) is pasted on the substrate, mortar is applied on the polystyrene insulation board, and the mortar is fully dried at room temperature to obtain a mortar layer;

[0084] (3) coating the hydrophobic primer obtained in step (1) on the mortar layer obtained in step (2), and drying at room temperature for 10 hours to obtain a hydrophobic primer layer; coating putty on the hydrophobic primer layer, and curing at room temperature for 24 hours to obtain a putty layer;

[0085] (4) coating the waterproof primer obtained in step (1) on the putty layer obtained in step (3), drying at room temperature for 8 hours and then coating the primer, drying the primer layer at room temperature for 10 hours and then coating the topcoat, and drying at room temperature for 12 hours to obtain the anti-efflorescence composite layer.

[0086] Example 2

[0087] An anti-efflorescence composite layer, the structural schematic diagram is as follows Figure 1 As shown, the following layers are arranged in sequence:

[0088] Insulation layer 1, thickness 35mm, polystyrene insulation board;

[0089] Mortar layer 2, thickness 3 mm, made of the same material as in Example 1;

[0090] The hydrophobic primer layer 3 has a thickness of 18 μm, and the materials of the hydrophobic primer layer include, by weight: 50 parts of acrylic emulsion, 4 parts of film-forming aid, 1.5 parts of organosilicon hydrophobic agent, 0.2 parts of defoaming agent, 1.5 parts of antifreeze agent and 0.2 parts of preservative;

[0091] Putty layer 4, thickness is 1 mm, and the material is the same as that in Example 1;

[0092] The waterproof primer layer 5 has a thickness of 8 μm, and the materials of the waterproof primer layer include, by weight: 40 parts of acrylic waterproof emulsion, 1.2 parts of film-forming aid, 0.5 parts of antifreeze agent, 0.1 parts of defoaming agent and 0.1 parts of preservative;

[0093] Primer layer 6, with a thickness of 15 μm and made of the same material as in Example 1;

[0094] The topcoat layer 7 has a thickness of 80 μm and is made of the same material as that in Example 1.

[0095] The preparation method of the anti-efflorescence composite layer is the same as that of Example 1.

[0096] Example 3

[0097] An anti-efflorescence composite layer, the structural schematic diagram is as follows Figure 1 As shown, the following layers are arranged in sequence:

[0098] Insulation layer 1, thickness 70mm, polystyrene insulation board;

[0099] Mortar layer 2, thickness 3 mm, made of the same material as in Example 1;

[0100] The hydrophobic primer layer 3 has a thickness of 8 μm, and the materials of the hydrophobic primer layer include, by weight: 30 parts of acrylic emulsion, 1 part of film-forming aid, 0.8 parts of organosilicon hydrophobic agent, 0.1 parts of defoaming agent, 0.8 parts of antifreeze agent and 0.1 parts of preservative;

[0101] Putty layer 4, thickness is 2 mm, made of the same material as in Example 1;

[0102] The waterproof primer layer 5 has a thickness of 18 μm, and the materials of the waterproof primer layer include, by weight: 60 parts of acrylic waterproof emulsion, 2.5 parts of film-forming aid, 1.5 parts of antifreeze agent, 0.2 parts of defoamer and 0.2 parts of preservative;

[0103] Primer layer 6, with a thickness of 10 μm and made of the same material as in Example 1;

[0104] The topcoat layer 7 has a thickness of 100 μm and is made of the same material as that in Example 1.

[0105] The preparation method of the anti-efflorescence composite layer is the same as that of Example 1.

[0106] Example 4

[0107] An anti-efflorescence composite layer, which differs from Example 1 only in that the thickness of the hydrophobic primer layer is 3 μm; other hierarchical structures, materials and preparation methods are the same as those in Example 1.

[0108] Example 5

[0109] An anti-efflorescence composite layer, which differs from Example 1 only in that the thickness of the hydrophobic primer layer is 25 μm; other hierarchical structures, materials and preparation methods are the same as those in Example 1.

[0110] Example 6

[0111] An anti-efflorescence composite layer, which differs from Example 1 only in that the thickness of the waterproof primer layer is 3 μm; other layer structures, materials and preparation methods are the same as those in Example 1.

[0112] Example 7

[0113] An anti-efflorescence composite layer, which differs from Example 1 only in that the thickness of the waterproof primer layer is 25 μm; other layer structures, materials and preparation methods are the same as those in Example 1.

[0114] Example 8

[0115] An anti-efflorescence composite layer, which differs from Example 1 only in that the materials of the hydrophobic primer layer include, by weight, 40 parts of acrylic emulsion, 2 parts of film-forming aid, 4 parts of silicone hydrophobic agent, 0.1 part of defoaming agent, 1 part of antifreeze agent and 0.1 part of preservative; other hierarchical structures, materials and preparation methods are the same as those in Example 1.

[0116] Example 9

[0117] An anti-efflorescence composite layer, which differs from Example 1 only in that the materials of the hydrophobic primer layer include, by weight, 40 parts of acrylic emulsion, 2 parts of film-forming aid, 0.1 parts of defoaming agent, 1 part of antifreeze agent and 0.1 parts of preservative; other hierarchical structures, materials and preparation methods are the same as those in Example 1.

[0118] Example 10

[0119] An anti-efflorescence composite layer, which differs from Example 1 only in that the materials of the waterproof primer layer include, by weight, 50 parts of acrylic emulsion (Badford AT, glass transition temperature of -20°C, number average molecular weight of 980,000, water absorption greater than 1.1%), 2 parts of film-forming aid, 1 part of antifreeze agent, 0.1 part of defoaming agent and 0.1 part of preservative; other hierarchical structures, materials and preparation methods are the same as those in Example 1.

[0120] Comparative Example 1

[0121] An anti-efflorescence composite layer, which differs from Example 1 only in that it does not contain a hydrophobic primer layer, that is, it includes a 50mm insulation layer, a 2mm mortar layer, a 2mm putty layer, a 10μm waterproof primer layer, a 10μm primer layer and a 90μm topcoat layer arranged in sequence.

[0122] Comparative Example 2

[0123] An anti-efflorescence composite layer, which differs from Example 1 only in that it does not contain a waterproof primer layer, that is, it includes a 50mm insulation layer, a 2mm mortar layer, a 10μm hydrophobic primer layer, a 2mm putty layer, a 10μm primer layer and a 90μm topcoat layer arranged in sequence.

[0124] Comparative Example 3

[0125] An anti-efflorescence composite layer, which differs from Example 1 only in that it does not contain a hydrophobic primer layer and a waterproof primer layer, that is, it includes a 50mm insulation layer, a 2mm mortar layer, a 2mm putty layer, a 10μm primer layer and a 90μm topcoat layer arranged in sequence.

[0126] The anti-efflorescence performance of the anti-efflorescence composite layers provided in Examples 1 to 10 and Comparative Examples 1 to 3 was tested, and the specific testing method was as follows:

[0127] (1) Treatment method: After a 30 cm long cotton thread is fully moistened in water, one end of the cotton thread is pasted on the coating to be tested, and the other end is immersed in a 1 L plastic bottle filled with water. The water in the plastic bottle is conducted through the cotton thread to slowly soak the coating to be tested. After 24 hours, the alkali efflux of the coating is observed;

[0128] (2) Result determination: The anti-efflorescence performance is determined by the area of ​​efflorescence on the tested coating. If the proportion of efflorescence area in the entire coating test area is less than 10%, it is qualified; if the proportion of efflorescence area in the entire coating test area is less than 5%, it is excellent.

[0129] For example, the alkali efflorescence test comparison diagram of the anti-efflorescence composite layer of Example 1 and Comparative Example 1 is as follows: Figure 2 As shown, Figure 2 The dotted circled area represents the efflorescence area. Figure 2 It can be seen that the efflorescence area of ​​the anti-efflorescence composite layer in Example 1 is less than 5%, which is significantly lower than that in Comparative Example 1, and has excellent anti-efflorescence performance.

[0130] The specific test results are shown in Table 1.

[0131] Table 1

[0132]

[0133] According to the performance test data of Table 1, the anti-efflorescence composite layer provided in Examples 1 to 3 of the present invention is screened by coating materials and designed by hierarchical structure, especially by the mutual cooperation of hydrophobic primer layer and waterproof primer layer, so that the coating has excellent anti-efflorescence performance, the efflorescence area is less than 10%, and can even be as low as 2%, and the anti-efflorescence composite layer has good construction performance, and has good recoatability and interlayer adhesion between the layers, and good mechanical properties. It can be seen from the parallel comparison examples 1, 4 to 7 that the hydrophobic primer layer and the waterproof primer layer are combined within a suitable thickness range, and further optimization of anti-efflorescence performance can be achieved. If the thickness of the hydrophobic primer layer is too small, it will affect the hydrophobic effect, which is not conducive to anti-efflorescence performance; if the thickness of the hydrophobic primer layer is too large, although the anti-efflorescence performance is very good, it will have a negative impact on the adhesion of the next coating (putty layer). The waterproof primer layer can effectively block the entry of external water, and the coating is too thin, which is not conducive to blocking moisture, and the coating is too thick, which will cause the strength of the composite layer to decrease, affecting mechanical properties.

[0134] In the anti-efflorescence composite layer provided by the present invention, the hydrophobic primer layer is matched with an acrylic emulsion and an organosilicon hydrophobic agent in a specific ratio to give the coating excellent hydrophobic and water-isolating properties; if the organosilicon hydrophobic agent is not contained (Example 9), the anti-efflorescence performance of the composite layer will drop sharply; if the amount of the organosilicon hydrophobic agent is too high (Example 8), the surface energy of the formed hydrophobic primer layer is too low, which affects the recoatability of the putty layer and reduces the construction performance. In addition, if the water absorption rate of the acrylic emulsion in the waterproof primer layer is too high (Example 10), it is difficult to effectively block the entry of external water vapor, causing serious efflorescence of the composite layer.

[0135] The present invention can completely isolate water vapor from both inside and outside by reasonably setting the hydrophobic primer layer and the waterproof primer layer, thereby preventing the occurrence of efflorescence. Figure 2 It can be seen that the lack of any hierarchical structure in Comparative Examples 1 to 3 will lead to serious alkali efflorescence of the coating, which cannot meet the application requirements in architectural coating.

[0136] The applicant declares that the present invention uses the above embodiments to illustrate an anti-efflorescence composite layer and its preparation method and application, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An anti-efflorescence composite layer, characterized in that: The anti-efflorescence composite layer comprises a thermal insulation layer, a mortar layer, a hydrophobic primer layer, a putty layer, a waterproof primer layer, a primer layer and a topcoat layer which are arranged in sequence; The material of the hydrophobic primer layer is a hydrophobic primer, which comprises the following components by weight: 30-50 parts of acrylic emulsion, 0.5-5 parts of film-forming aid, 0.1-2 parts of organosilicon hydrophobic agent, 0.01-0.3 parts of defoaming agent, 0.1-3 parts of antifreeze agent and 0.01-0.3 parts of preservative; the acrylic emulsion comprises pure acrylic emulsion and / or styrene acrylic emulsion; the film-forming aid is an alcohol ester film-forming aid; the organosilicon hydrophobic agent comprises polysiloxane; The material of the waterproof primer layer is a waterproof primer, which includes 40-60 parts of acrylic waterproof emulsion, 0.5-5 parts of film-forming aid, 0.1-3 parts of antifreeze agent, 0.01-0.3 parts of defoamer and 0.01-0.3 parts of preservative in parts by weight; the film-forming aid is an alcohol ester film-forming aid; The primer layer is an acrylic primer layer; the material of the topcoat layer is a water-based acrylic topcoat.

2. The anti-efflorescence composite layer according to claim 1, characterized in that: The thickness of the thermal insulation layer is 30 to 80 mm.

3. The anti-efflorescence composite layer according to claim 1, characterized in that: The thermal insulation layer is a polystyrene thermal insulation board.

4. The anti-efflorescence composite layer according to claim 1, characterized in that: The thickness of the mortar layer is 2 to 3 mm.

5. The anti-efflorescence composite layer according to claim 1, characterized in that: The material of the mortar layer includes a combination of silicate cement, quartz sand and glue powder.

6. The anti-efflorescence composite layer according to claim 1, characterized in that: The thickness of the hydrophobic primer layer is 5 to 20 μm.

7. The anti-efflorescence composite layer according to claim 1, characterized in that: The thickness of the putty layer is 1 to 2 mm.

8. The anti-efflorescence composite layer according to claim 1, characterized in that: The material of the putty layer includes a combination of silicate cement, heavy calcium powder and rubber powder.

9. The anti-efflorescence composite layer according to claim 1, characterized in that: The thickness of the waterproof primer layer is 5 to 20 μm.

10. The anti-efflorescence composite layer according to claim 1, characterized in that: The water absorption rate of the acrylic waterproof emulsion is 0 to 0.1%.

11. The anti-efflorescence composite layer according to claim 1, characterized in that: The number average molecular weight of the acrylic waterproof emulsion is 800,000 to 1.2 million.

12. The anti-efflorescence composite layer according to claim 1, characterized in that: The glass transition temperature of the acrylic waterproof emulsion is -15 to 0°C.

13. The anti-efflorescence composite layer according to claim 1, characterized in that: The thickness of the primer layer is 5 to 20 μm.

14. The anti-efflorescence composite layer according to claim 1, characterized in that: The thickness of the topcoat layer is 80-100 μm.

15. A method for preparing an anti-efflorescence composite layer according to any one of claims 1 to 14, characterized in that: The preparation method comprises the following steps: (1) After attaching the insulation board to the substrate, apply mortar on the insulation board and dry it to obtain a mortar layer; (2) coating a hydrophobic primer on the mortar layer obtained in step (1), drying the mortar layer, and obtaining a hydrophobic primer layer; coating putty on the hydrophobic primer layer, curing the mortar layer, and obtaining a putty layer; (3) coating a waterproof primer on the putty layer obtained in step (2), and coating a primer after drying; coating a topcoat after the primer layer obtained is dried, and drying to obtain the anti-efflorescence composite layer.

16. The preparation method according to claim 15, characterized in that: The substrate in step (1) is a wall.

17. The preparation method according to claim 15, characterized in that: The drying time in step (1) is 0.5 to 15 hours.

18. The preparation method according to claim 15, characterized in that: The drying time in step (2) is 0.5 to 15 hours.

19. The preparation method according to claim 15, characterized in that: The curing time in step (2) is 12 to 48 hours.

20. Use of the anti-efflorescence composite layer according to any one of claims 1 to 14 in painting of building walls.

21. The use according to claim 20, characterized in that The building wall is an outer wall of the building.

Citation Information

Patent Citations

  • Water-based alkali-resistant and salting-out resistant close primer

    CN103483968A

  • Long-acting anti-efflorescence primer and preparation method thereof

    CN105440853A

  • Alkali-resistant primer for external wall and preparation method of alkali-resistant primer

    CN105482570A

  • Anti-efflorescence composite structure

    CN215167401U